2022
DOI: 10.1371/journal.pone.0275816
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping of UK Biobank clinical codes: Challenges and possible solutions

Abstract: Objective The UK Biobank provides a rich collection of longitudinal clinical data coming from different healthcare providers and sources in England, Wales, and Scotland. Although extremely valuable and available to a wide research community, the heterogeneous dataset contains inconsistent medical terminology that is either aligned to several ontologies within the same category or unprocessed. To make these data useful to a research community, data cleaning, curation, and standardization are needed. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Furthermore, these results are consistent with prior work highlighting challenges with UK Biobank clinical codes [20]. Specifically, Stroganov et al highlighted mapping issues of available hospital inpatient and general practitioner information onto the ICD-10 ontology [20]. The limited classification accuracy for most ICD-10 diagnostic groups observed in this study furthermore confirms previous work suggesting that the identification of biomarkers of psychopathology is not feasible without increased efforts to address suboptimal phenotypic reliability [11].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, these results are consistent with prior work highlighting challenges with UK Biobank clinical codes [20]. Specifically, Stroganov et al highlighted mapping issues of available hospital inpatient and general practitioner information onto the ICD-10 ontology [20]. The limited classification accuracy for most ICD-10 diagnostic groups observed in this study furthermore confirms previous work suggesting that the identification of biomarkers of psychopathology is not feasible without increased efforts to address suboptimal phenotypic reliability [11].…”
Section: Discussionsupporting
confidence: 88%
“…This conclusion corroborates past work on low inter-rater reliability in ICD-10 coding, which may be driven by many factors including patient-provider communication, administrative decision chains, and insurance incentives [8]. Furthermore, these results are consistent with prior work highlighting challenges with UK Biobank clinical codes [20]. Specifically, Stroganov et al highlighted mapping issues of available hospital inpatient and general practitioner information onto the ICD-10 ontology [20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For instance, in method 1, errors occur during translation from ICD-10-CM to SNOMED, while in method 2, issues arise from incomplete coverage and accuracy of the WHO map from ICD-10-CM to ICD-11. Additionally, studies focus on translating Read codes [5]. The examination revealed that achieving a lossless correspondence between Read codes and the ICD10-CM disease coding system is unattainable due to disparities in ontologies and insurmountable ambiguity in the utilization of the Read code system by medical professionals [5].…”
Section: Introductionmentioning
confidence: 99%